2003
DOI: 10.1034/j.1600-0501.2003.120906.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone contact, growth, and density around immediately loaded implants in the mandible of mini pigs

Abstract: The aim of the study was to compare the bone mineral apposition rate (BMAR) of immediately loaded implants with an unloaded control during the early healing phase in the partially edentulous mandible. In seven mini pigs, three premolars and the first molar were removed in the left mandible. Three months later, five implants were installed. Four implants received a fixed provisional restoration and were loaded immediately. The most anterior implant was used as unloaded control. Polychromatic fluorescence labell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 28 publications
8
81
0
10
Order By: Relevance
“…These factors include systemic condition of the patient, bone quality and quantity, cantilever forces, occlusal load direction, and position of implant. 26,27 Nkenke et al 28 found that immediate loading does not affect the bone mineral apposition rate when compared with unloaded implants if all conditions are under control. After 4 months of placement of implant, the bone-to-implant contact was 77.8% for the loaded and 78.0% for the unloaded implants.…”
Section: Introductionmentioning
confidence: 99%
“…These factors include systemic condition of the patient, bone quality and quantity, cantilever forces, occlusal load direction, and position of implant. 26,27 Nkenke et al 28 found that immediate loading does not affect the bone mineral apposition rate when compared with unloaded implants if all conditions are under control. After 4 months of placement of implant, the bone-to-implant contact was 77.8% for the loaded and 78.0% for the unloaded implants.…”
Section: Introductionmentioning
confidence: 99%
“…The pigs were provided by Lahav C.R.O (Kibbutz Lahav, Israel). Pigs are considered to be a good nonhuman model for better understanding human skeletal and dental questions such as osteonecrosis of the femoral head, bone fractures, bone growth, and development, as well as for evaluating new dental implant designs (Buser et al, 1991;An and Freidman, 1998;Terheyden et al, 1999;Nkenke et al, 2003). While porcine bones in general have a denser trabecular network than human trabecular networks (Mosekilde et al, 1993), porcine bone shows similarities to human bone in terms of bone biology (modeling and remodeling), as well as bone mineral density (Mosekilde et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the oral maxillo-facial region of these animals is similar to that of humans in anatomy, development, physiology, pathophysiology, and disease occurrence [22]. For this reasons, we and others consider these animals as a good preclinical model for bone disease and also for maxillofacial research; indeed, in the last years, they have been already used for pre-clinical study in dental implantology [16,23,24] and maxillo-facial surgery [25][26][27]. In this study, we analyzed two different bone substitutes: one is an implantable, reabsorbable, non-active, Class III medical device, specifically used as a scaffold for bone defect reconstruction.…”
mentioning
confidence: 99%